Remoção biológica de nitrogênio de efluente de abatedouro bovino em reator em batelada sequencial - Lima, Adriana Neres de (2012)
Agroindustrial effluents from meat processing are characterized by high levels of suspended solids, organic compounds and nutrients, mainly nitrogen on its different forms. It is crucial to remove nitrogen compounds from these effluents because of its eutrophying potential and risks to aquatic life as well as to human health. Thus, this trial aimed at evaluating the efficiency of a sequencing batch reactor (SBR), as a post-treatment, on biological removal of nitrogen in cattle slaughterhouse wastewater by nitrification/denitrification processes. The experimental unit consisted of a SBR made of polyethylene with 185 mm diameter x 205 mm height and a 4 L working volume. The effects of initial concentration of ammoniacal nitrogen were investigated at 100, 150 and 200 mg L-1 and air flow rate of 0.125, 0.375 and 0.625 L min-1 Lreactor -1 on nitrogen compounds removal. A central rotatable composite design (CRCD) was applied with four runs in -1 and +1 levels, four runs on levels of axial points (-1.414 and +1.414) and three replications at the central point (0). Nitrification performance was evaluated according to the efficiency of nitrogen ammoniacal removal, conversion of nitrite to nitrate and nitrite accumulation (%), denitrification performance based on the efficiency of nitrite/nitrate and organic matter (%) removal, as well as the efficiency of the whole process by the removal of total nitrogen (%). During the treatment system management, the observed parameters were: temperature, pH, alkalinity, dissolved oxygen, C/N ratio, free ammonia and nitrous acid. During nitrification process, there were changes among 11.5 and 100%, 9.2 and 94.9% and 4.0 and 19.6% in order to have an efficient removal of ammoniacal nitrogen, conversion of ammoniacal nitrogen to nitrate and nitrite concentration, respectively. Nitrite concentration of less than 20% may be a clue of a complete nitrification. Both studied factors, initial concentration of ammoniacal nitrogen and air flow rate, showed significant effects at 10% on the recorded variables response, although the interaction among factors showed no significance. The increased air flow and decrease concerning the initial concentration of ammoniacal nitrogen resulted in higher efficiencies of ammoniacal and total nitrogen removal, as well as the conversion of ammoniacal nitrogen to nitrate. During the preestablished intervals of this study, the highest efficiencies above 80% were achieved in air flow levels between 0.375 and 0.725 L min-1 Lreactor -1 and initial concentration of ammoniacal nitrogen between 80 and 200 mg L-1. On denitrification process, the answers ranged from 91.5 and 96.9 and 78.3% and 87.9% concerning the efficiencies to remove nitrite/nitrate and organic matter. The evaluation of kinetic behavior showed a possible reduction in cycle times of aerobic and anoxic phases, since removals of nitrogen compounds, superior to 90%, were achieved in only 12 and 1 h, respectively. Maximum concentrations, 13.8 and 6.8 x 10-9 mg L-1 of free ammonia and nitrous acid, did not inhibit ammoniacal nitrogen oxidation. The SBR system, used to remove nitrogen, proved to be feasible for the treatment of effluent from cattle slaughterhouse, as it has shown high levels of oxidation of nitrogen compounds that met the discharge standards, required by law